2019
DOI: 10.1016/j.adro.2019.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Escalated Intensity Modulated Radiation Therapy for Prostate Cancer: 15-Year Outcomes Data

Abstract: Purpose To report 15-year outcomes for dose-escalated intensity modulated radiation therapy (IMRT) for localized prostate cancer (PC) by evaluating biochemical relapse, distant metastases, cancer-specific survival, and long-term toxicity. Methods and materials A database search was conducted for the first cohort of patients treated at this institution with 81 or 86.4 Gy between 1996 and 1998 using IMRT. Toxicity data were scored according to the Common Terminology Crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Standard fractionation EBRT for treatment of prostate cancer is delivered using daily radiation doses of 1.8-2 Gy, five days a week, over 8-10 weeks, up to a total dose of 86.4 Gy [7]. The radiobiologic characteristics of prostate cancer, which has low alpha/beta ratio, provided the theoretical basis for hypofractionated RT [8].…”
Section: Introductionmentioning
confidence: 99%
“…Standard fractionation EBRT for treatment of prostate cancer is delivered using daily radiation doses of 1.8-2 Gy, five days a week, over 8-10 weeks, up to a total dose of 86.4 Gy [7]. The radiobiologic characteristics of prostate cancer, which has low alpha/beta ratio, provided the theoretical basis for hypofractionated RT [8].…”
Section: Introductionmentioning
confidence: 99%
“…We used the validated CPG 4 to discriminate between risk groups (Figure 1). With recurrence rates of 2.5%, 14.3%, 24.0%, and 40.5% for CPGs 2 to 5, respectively, this stratification tool identified a clear link between recurrence risk and pretreatment patient and tumor characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation therapy (RT) combined with long‐term androgen deprivation therapy (ADT) is a standard of care option for men with high‐risk and locally advanced prostate cancer (PCa). Several studies have additionally demonstrated that dose escalation improves biochemical tumor control outcomes 1‐4 . However, higher doses of RT also results in increased rates of toxicity with five‐year late grade ≥2 gastrointestinal and genitourinary toxicity rates ranging from 12% to 15% 5 …”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancer is the most prevalent non-cutaneous malignancy among men [1]. External Beam radiation therapy (EBRT) for prostate cancer using conventional fractionation provides 1.8-2 Gy per fraction every day, 5 days a week, over 7-10 weeks [2]. Image guided radiation therapy (IGRT) is usually utilized for EBRT as the prostate location can change relative to the pelvic bones, as a function of rectal and bladder filling.…”
Section: Introductionmentioning
confidence: 99%
“…Image guided radiation therapy (IGRT) is usually utilized for EBRT as the prostate location can change relative to the pelvic bones, as a function of rectal and bladder filling. Implantation of at least 3 fiducial markers in the prostate enables three dimensional localization of the prostate using daily 2D-kV or cone beam computerized tomography (CBCT) [2].…”
Section: Introductionmentioning
confidence: 99%